2022
DOI: 10.1097/j.pain.0000000000002647
|View full text |Cite
|
Sign up to set email alerts
|

“Listen to me, learn from me”: a priority setting partnership for shaping interdisciplinary pain training to strengthen chronic pain care

Abstract: Supplemental Digital Content is Available in the Text.This empirically derived framework strongly repositions shaping of health workforce training through a genuine partnership lens, strengthening training efforts to support high-quality, person-centred, chronic pain care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 71 publications
0
16
0
1
Order By: Relevance
“…They suggested that the messages provided by pain education should be consistent between practitioners and across the community to reduce uncertainty and confusion for patients about the best management approach (Schneiderhan et al 2017). GP education was seen as vital by participants in this study, aligning with the recommendations of the Australian National Strategic Action Plan for Pain Management, which identifies clinician education as a priority (Slater et al 2022).…”
Section: Discussionmentioning
confidence: 72%
“…They suggested that the messages provided by pain education should be consistent between practitioners and across the community to reduce uncertainty and confusion for patients about the best management approach (Schneiderhan et al 2017). GP education was seen as vital by participants in this study, aligning with the recommendations of the Australian National Strategic Action Plan for Pain Management, which identifies clinician education as a priority (Slater et al 2022).…”
Section: Discussionmentioning
confidence: 72%
“…Similar priorities have been seen in paediatric chronic pain research and general chronic pain care. 3,32 The least used intervention in our study was the interdisciplinary intervention. From previous priority setting partnership studies, it is known that an increased focus on improving interdisciplinary care is warranted across both the broad domain of chronic MSK pain, common hand and wrist conditions, fractures of the lower limb, and knee arthroplasty.…”
Section: Comparison With Priority Setting Partnershipsmentioning
confidence: 99%
“…Clinicians may intentionally avoid discussing mental health owing to a lack of training and practice (feelings of inadequacy), discomfort with mental health topics, and fear of offending the patient, among other reasons [3,28,32,42,45]. Although some patients may misinterpret a musculoskeletal specialist's intentions when a discussion about thoughts and feelings is raised, there is some evidence that most people welcome it and may feel the lack of it [12,14,34]. A few bad experiences might skew surgeon behavior toward not addressing unhelpful thinking and feelings of worry or despair.…”
Section: Rationalementioning
confidence: 99%